The economic policy trends in Iraq beyond 2003 - فتاح عبد الجبار محمود; منير عامر سامي (Journal of Economics and Administrative Sciences, 2015)
Gaining economic policy of exceptional importance in severe unilateral Iraqi economy such as the economy, as oil revenues constitute the center of gravity in the internal and external balances, Economic policy have seen in Iraq beyond 2003 in absentia economic strategic vision and failure in the application of policies to achieve economic development, as there was a disconnect and lack of integration and coordination between macro policies of monetary policy and fiscal policy, especially as if they were floating two policies are not linked by a link